2021
DOI: 10.3389/fncel.2021.665596
|View full text |Cite
|
Sign up to set email alerts
|

Improving NKCC1 Function Increases the Excitability of DRG Neurons Exacerbating Pain Induced After TRPV1 Activation of Primary Sensory Neurons

Abstract: Background Our aim was to investigate the effects of the protein expression and the function of sodium, potassium, and chloride co-transporter (NKCC1) in the dorsal root ganglion (DRG) after activation of transient receptor potential vanilloid 1 receptor (TRPV1) in capsaicin-induced acute inflammatory pain and the possible mechanism of action.Methods Male Sprague–Dawley rats were randomly divided into control, capsaicin, and inhibitor groups. The expression and distribution of TRPV1 and NKCC1 in rat DRG were o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…A recent report shows that activation of TRPV1 by exogenous agonists can increase the expression and function of the NKCC1 protein in DRGs, which is mediated by the activation of the PKC/pERK signaling pathway. 43 This needs to be confirmed in future studies. Although more experiments are needed, our data have provided evidence to demonstrate that changes in the peripheral nervous system also play a major role in promoting pain sensitization after SCI.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…A recent report shows that activation of TRPV1 by exogenous agonists can increase the expression and function of the NKCC1 protein in DRGs, which is mediated by the activation of the PKC/pERK signaling pathway. 43 This needs to be confirmed in future studies. Although more experiments are needed, our data have provided evidence to demonstrate that changes in the peripheral nervous system also play a major role in promoting pain sensitization after SCI.…”
Section: Discussionmentioning
confidence: 88%
“…[40][41][42] Intrathecal delivery of the NKCC1 antagonist BU decreased the concentration of chloride in the DRGs and inhibited the hyperalgesia caused by capsaicin. 43 An in vitro study found that inflammatory mediators increase the NKCC1 channel expression of DRGs within three hours. 44 Taken together, these findings indicate that the NKCC1 of DRGs might be an important player in pain.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanistically, the basis of the reduction in ADS in C-fibres after inflammation has not been determined. However, this could be related to an elevation of intracellular chloride that occurs in DRG neurons [ 56 ] upon increased phosphorylation of NKCC1 following inflammation [ 27 ]. Our previous work has shown that ADS is increased by both the conditional deletion of GABA A -R in NaV1.8 + neurons and the NKCC1 blockade while, akin to CFA, GABA A -R agonists reduce ADS [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…To achieve this, key pathways are blocked/activated by pharmacological means, such as the P2X4-BDNF-KCC2 pathway ( Ferrini et al, 2013 ; Romeo-Guitart and Casas, 2020 ), BDNF-trkb ( Miletic and Miletic, 2008 ; Rivera et al, 2002 ; Rivera et al, 2004 ; Huang et al, 2017 ; Wenner, 2014 ; Sánchez-Brualla et al, 2018 ) or direct regulation of KCC2 activity, such as N and C termin ( Ferrini et al, 2013 ) N-terminal loop Chi et al, 2021, phosphorylation of serine 940 ( Leonzino et al, 2016 ) will likely be potential targets for clinical treatment of spinal cord injury and its complications. In addition, through exercise training, modulation of the 5-HTergic system ( Bos et al, 2013 ; Sánchez-Brualla et al, 2018 ; Ryu et al, 2021 ), the GABAergic system, and TRPV1 ( Deng et al, 2021 ) to indirectly affect NKCC1 and KCC2 expression levels are also feasible intervention strategies. The targeted regulation of different types of neurons may become a future treatment strategy for SCI and its complications ( Chen et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Transient receptor potential vanilloid 1 (TRPV1) is an important protein in the perception of pain ( Takayama et al, 2015 ) and its expression in the dorsal horn of the spinal cord is an essential link in the emergence of neuropathic pain after SCI ( Wu et al, 2013 ; Lee et al, 2021 ). The regulation of NKCC1 expression mediated by TRPV1 through the activation of the PKC/phosphorylated extracellular signal-regulated kinase (pERK) signaling pathway may be the mechanism underlying its involvement in SCI-related neuropathic pain ( Deng et al, 2021 ).…”
Section: Kcc2/nkcc1 and Spinal Cord Injurymentioning
confidence: 99%